2023
DOI: 10.1097/js9.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Trocar number and placement for laparoscopic sleeve gastrectomy and comparison of single-incision and conventional laparoscopic sleeve gastrectomy: a systematic review and meta-analysis

Abstract: Background: Conventional laparoscopic sleeve gastrectomy (CLSG) has been conducted in multiple centers for treating morbid obesity, however, there are no standard criteria for (1) placing the trocar; and (2) how many trocars should be used. Single-incision laparoscopic sleeve gastrectomy (SLSG), a newly emerged technique in 2008, has been proposed as an alternative to CLSG in recent years, however, there is no definite evidence for this. Materials and methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…For CLSG procedures, they found that most studies utilized either four or five trocars arranged in an inverted trapezoid pattern, favoring the left side. A comparison between SLSG and CLSG showed a significantly longer operative time for SLSG but with lower pain scores on postoperative day 1 1 . There were no differences in other perioperative outcomes such as complications 1 .…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…For CLSG procedures, they found that most studies utilized either four or five trocars arranged in an inverted trapezoid pattern, favoring the left side. A comparison between SLSG and CLSG showed a significantly longer operative time for SLSG but with lower pain scores on postoperative day 1 1 . There were no differences in other perioperative outcomes such as complications 1 .…”
mentioning
confidence: 95%
“…A comparison between SLSG and CLSG showed a significantly longer operative time for SLSG but with lower pain scores on postoperative day 1 1 . There were no differences in other perioperative outcomes such as complications 1 . This is an important area of research, as bariatric surgery is gaining popularity as an effective treatment for obesity-related diseases.…”
mentioning
confidence: 95%
See 3 more Smart Citations